‘What is the use of talking-talking?’ Reflections on talking, silence, and resilience in Sierra Leone - Friederike Mieth (Acta Academica, 2015)
When conducting research on how Sierra Leoneans dealt with the past of a civil war in their everyday lives, I often observed that my informants felt that talking about the war was no longer necessary, especially in public situations. Moreover, many told me that it was better to ‘forget’ and move on. Speaking about such attitudes at conferences or workshops in Europe, I often received sceptical comments, suggesting that Sierra Leoneans seem ‘not yet ready’ to deal with their violent past and that this could not be healthy in the long term. Inspired by these reactions, I ask  whether ‘not talking’ about experiences of violence is unhealthy. To answer this question, I draw on psychological studies on resilience that examine the factors that help individuals cope successfully with adversity. I find that the role of ‘talking’ may be of lesser relevance for the well-being of those who have experienced mass violence. Rather, various individual, social, and cultural factors contribute to resilience. The reflections in this article is intended to encourage further research on the different ways in which people cope with adversity.